ChemInform Abstract: A Review of the Iron—Air Secondary Battery for Energy Storage. Issue 14 (April 2015) - McKerracher, R. D.; Ponce de Leon, Carlos; Wills, R. G. A.; Shah, A. A.; Walsh, Frank C.
Abstract: Review: 82 refs.